The Role of Advocates in Providing Legal Assistance to Criminals Who Assist in Carrying Out Child Sexual Exploitation - Anbiya Hidayatullah, Sakti; Winjaya Laksana, Andri (UNISSULA Semarang, 2025)
This study aims to examine and analyze the role of advocates in providing legal assistance to perpetrators of crimes that help carry out sexual exploitation of children, obstacles and solutions. This study uses a sociological juridical approach method, analytical descriptive research specifications. The data used are primary data and secondary data. Data collection methods include field studies and literature studies, and the data analysis method is qualitative. The theories used in this study are the theory of the legal system, and the theory of authority. The role of advocates in providing legal assistance to perpetrators of crimes that help carry out sexual exploitation of children is in line with applicable laws and regulations, namely the Advocates Law, the Criminal Procedure Code, and other relevant legal regulations. Obstacles faced by advocates in providing legal assistance to perpetrators of crimes that help carry out sexual exploitation of children are difficulties in communication/negotiation with law enforcement officers, the legal system not running well, difficulties in communicating with children when the client is a child.